DA’WAH-ORIENTED GOVERNANCE: THE INFLUENCE OF MANAGERIAL CHARACTERISTICS ON ISLAMIC SOCIAL REPORTING IN INDONESIA - Siti Malikah; Samsul Rosadi; Usnan (UIN Sunan Kalijaga, 2025)
The aim of this paper is to analyze the influence of CEO characteristics on Islamic Social Reporting (ISR) in Indonesia's Islamic banking sector during the period 2015–2020. The independent variables dealt with are CEO age, CEO business educational background, CEO gender, and CEO experience. The independent variables were tested against ISR as the dependent variable with multiple regression analysis. Findings from this study have shown that CEO age and CEO gender negatively and significantly influence the ISR, while CEO experience positively and significantly influences it. On the contrary, the CEO's business education background is not significantly related to the ISR. This could therefore provide very important contributions for both practitioners and researchers in comprehending the factors of Islamic social reporting practice in the Islamic banking sector of Indonesia. Such findings will also be used as a launching pad for future research involving wider samples and other methodological approaches that would increase insight into the dynamics of Islamic social reporting practices in Indonesia.